Investigasi Karakteristik Personal Auditor dalam Pendeteksian Kecurangan dengan Moderasi Tekanan Waktu - Christina, Christina; Dewi, Indira Shinta; Khoirunnisa, Vini (Universitas Pamulang, 2025)
This study intends to examine the effect of auditors' personal characteristics on fraud detection with time pressure as a moderator. Primary data obtained by a questionnaire is known as research data. Purposive sampling was utilized to collect the sample, with 100 respondents drawn from 25 KAPs in the South Jakarta region. Multiple linear regression analysis using SPSS version 26 is the data analysis technique employed. The study's findings show that while skill has little bearing on fraud detection, the personal traits of auditors such as audit experience and professional skepticism. However, the association between audit experience, skill, and professional skepticism toward fraud detection might be moderated by time constraints